Prioritising transport barriers and enablers to mobility in later life: A case study from Greater Manchester in the United Kingdom. (September 2021) - Musselwhite, Charles
Abstract: Introduction: There are many barriers to mobility for older people which are detrimental to older people's health and wellbeing. This research got older people to prioritise their transport barriers in terms of their importance as a barrier to getting out and about, and the likelihood that that barrier occurs locally to them. Following this, older people then co-developed and prioritised solutions to the barriers, prioritising them in terms of potential effectiveness and perceived ease of implementation. Methodology: Using a case study of Greater Manchester in the United Kingdom, a series of focus groups in different locations got older people and stakeholders to prioritise issues and solutions for older people's mobility around neighbourhood, public and community transport and policy and practice themes. Results: Participants tended to prioritise issues that affected their safety. Poor quality pavements, sharing pavements with cyclists and mobility scooters, poor crossing facilities and bus drivers driving off before they had a chance to sit down were all major issues and all related to the potential for falls. Poor information and signage was another issue with public and community transport. To help put things right, it was strongly suggested transport staff need age friendly awareness training. Participants also wanted more involvement with decision making over transport and the built environment with a need to move beyond the current forms of consultation. Conclusion: Overall, there was a constant tension between older people portraying themselves and being seen as frail and needy and as resourceful, proactive and engaged. This makes the transport offering difficult to achieve, schemes aimed at plugging deficits are seen as inappropriately patronising, yet schemes not aimed at older people can make them feel misunderstood or ignored. Highlights: Research determined barriers and enablers to transport for older people. Participants prioritised issues affecting safety. Solutions preferred involved training and involvement. Older people portray themselves as frail and needy yet also resourceful.